KAJIAN PUSTAKA PENGARUH PSEUDOPOLIMORF OBAT NSAID TERHADAP KELARUTAN, KECEPATAN DISOLUSI DAN STABILITAS SERTA PENGAMATAN PERILAKU HIDRAT NATRIUM - Saptarini Wharsana, Rora
Pseudopolymorph is a multi-component crystalline solid form of API and solvent molecule. Several NSAID drugs possess the pseudopolymorph form which can alter its physicochemical properties, such a solubility. One method to improve solubility is by salt formation. Weak acid APIs may form a salt with a strong base, such as Sodium Mefenamate (NM). This research aims to examine the effect of NSAID pseudopolymorphism on its solubility, dissolution rate, and stability. This research was then continued by the experiment of observing the pseudopolymorphism behaviour of NM toward heating and grinding for 3 hours, storage in the open air for 4 hours, and storage in a desiccator for 10 days. The characterization was done with electrothermal, FTIR, DTA/TG, DSC, and PXRD instruments to observe the hydration or dehydration process of NM pseudopolymorph. The literature review result was that a large number of NSAID pseudopolymorphs possess low solubility and low dissolution rate compared to its anhydrous form or even other polymorphs. The experiment result was that the NM pseudopolymorph was NM trihydrate. Heating at 100°C for 3 hours may dispel the water molecules completely forming anhydrous NM, while grinding for 3 hours manually cannot dispel the water molecules significantly. The anhydrous NM is unstable when stored in room condition with 25±1°C and RH 75±5% for 4 hours, the solid form tends to hydrate due to environmental moisture. The anhydrous NM is unstable when stored inside the desiccator for 10 days, reverting to the stable hydrate form during storage. According to this research, S, trihydrate is the most stable form during the storage period within the room condition and inside the desiccator. With the usage of SM trihydrate, the weight of water molecules needs to be considered to obtain the right dosage. Drying at 100°C for 3 hours may also produce anhydrous NM.